Improvisational Aesthetics: Byron, the Shelley Circle, and Tommaso Sgricci - Esterhammer, Angela (Romanticism on the Net)

(untitled) (Université de Montréal, 2006)
AbstractThe sensational Tommaso Sgricci (1789-1836), the most famous improvvisatore of his day, was known for theatrical performances in which he extemporized lyric poems as well as entire Classical dramas. His fame spread throughout Europe through periodical articles and reviews, and through the first-hand reports of English travellers who witnessed his performances in Italy. The Shelleys’ intense engagement with Sgricci during the winter of 1820-21 leaves its mark on important texts written during those years, including Mary’s Valperga and Percy’s Defence of Poetry. Byron encountered Sgricci both personally and professionally between 1816 and 1820; resonances between Sgricci’s distinctive performance genre and Byron’s later poetry are less direct, but more profound. The embodied responses to history in Canto IV of Childe Harold’s Pilgrimage bear comparison with Sgricci’s spontaneous dramas on Classical and historical themes, as does the “mobility” exemplified by the performer Lady Adeline Amundeville in the later cantos of Don Juan. Byron’s ability to “revivify” the past in these works may be illuminated by setting them alongside the practice of the improvvisatore, a figure who stands for the real-time, responsive, public process of crafting poetry out of contingent subject-matter, habitual sound-patterns, fragments of memory, and lively imagination.